2017
DOI: 10.24072/pci.evolbiol.100032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental change over geological time on the tempo and mode of biological diversification, revealed by Neotropical butterflies

Abstract: Cite as: Ree RH. 2017. The influence of environmental change over geological time on the tempo and mode of biological diversification, revealed by Neotropical butterflies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A recent assessment of diversification rates in the tribe revealed that a clade of eight species in the genus experienced an extremely rapid and recent radiation (Chazot et al, 2017) in agreement with previous studies using mitochondrial and nuclear genes, and rapidly evolving microsatellite markers, that show little genetic differentiation among taxa of this clade (Dasmahapatra, Lamas, Simpson, & Mallet, 2010;Elias et al, 2007;McClure & Elias, 2017;Whinnett et al, 2005). The Melinaea of north-eastern Peru (San Martín and Loreto departments) are of particular interest for speciation studies, as multiple species, many consisting of different subspecies, are present and overlap in distribution.…”
Section: Introductionmentioning
confidence: 99%
“…A recent assessment of diversification rates in the tribe revealed that a clade of eight species in the genus experienced an extremely rapid and recent radiation (Chazot et al, 2017) in agreement with previous studies using mitochondrial and nuclear genes, and rapidly evolving microsatellite markers, that show little genetic differentiation among taxa of this clade (Dasmahapatra, Lamas, Simpson, & Mallet, 2010;Elias et al, 2007;McClure & Elias, 2017;Whinnett et al, 2005). The Melinaea of north-eastern Peru (San Martín and Loreto departments) are of particular interest for speciation studies, as multiple species, many consisting of different subspecies, are present and overlap in distribution.…”
Section: Introductionmentioning
confidence: 99%